2021
DOI: 10.1085/jgp.202012814
|View full text |Cite
|
Sign up to set email alerts
|

The role of molecular diffusion within dendritic spines in synaptic function

Abstract: Spines are tiny nanoscale protrusions from dendrites of neurons. In the cortex and hippocampus, most of the excitatory postsynaptic sites reside in spines. The bulbous spine head is connected to the dendritic shaft by a thin membranous neck. Because the neck is narrow, spine heads are thought to function as biochemically independent signaling compartments. Thus, dynamic changes in the composition, distribution, mobility, conformations, and signaling properties of molecules contained within spines can account f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 166 publications
(196 reference statements)
0
16
0
Order By: Relevance
“…Spine shape involves local actin organization, second messengers, and organelles (e.g., endoplasmic reticulum and ribosomes, Yuste, 2010 ; Sala and Segal, 2014 ; Miermans et al, 2017 ; Okabe, 2020 ; for mitochondria see Li et al, 2004 ). This can lead to biochemical compartmentalization and affect the electrical signaling of synapses (Chen and Sabatini, 2012 ; Tønnesen and Nägerl, 2016 ; Obashi et al, 2021 ). The balance between spine number, structure, and function may represent synaptic processing for learning and memory (Bourne and Harris, 2007 , 2009 ) with stimulus-specific features (Knafo et al, 2005 ) in selective synaptic ensembles (Hayashi-Takagi et al, 2015 ).…”
Section: Brain Network Cellular Connectivity and The Relevance Of Den...mentioning
confidence: 99%
See 1 more Smart Citation
“…Spine shape involves local actin organization, second messengers, and organelles (e.g., endoplasmic reticulum and ribosomes, Yuste, 2010 ; Sala and Segal, 2014 ; Miermans et al, 2017 ; Okabe, 2020 ; for mitochondria see Li et al, 2004 ). This can lead to biochemical compartmentalization and affect the electrical signaling of synapses (Chen and Sabatini, 2012 ; Tønnesen and Nägerl, 2016 ; Obashi et al, 2021 ). The balance between spine number, structure, and function may represent synaptic processing for learning and memory (Bourne and Harris, 2007 , 2009 ) with stimulus-specific features (Knafo et al, 2005 ) in selective synaptic ensembles (Hayashi-Takagi et al, 2015 ).…”
Section: Brain Network Cellular Connectivity and The Relevance Of Den...mentioning
confidence: 99%
“…Therefore, synaptic integration made by each spine type can impact cellular activity differently depending upon its location and spatiotemporal processing along proximal to distal dendritic domains (Spruston et al, 2013 ). In addition, its passive and/or active biophysical properties associated with those of parent dendrites may play a role (Sala and Segal, 2014 ; Gidon et al, 2020 ; Obashi et al, 2021 ). Dendritic spines modulate both stable and/or transitory connections (Oray et al, 2006 ) and synaptic plasticity using various molecules in variable biochemical pathways for short-term to long-term cellular effects (Sala and Segal, 2014 ; Chidambaram et al, 2019 ).…”
Section: Brain Network Cellular Connectivity and The Relevance Of Den...mentioning
confidence: 99%
“…The logical conclusion to draw from this seems to be that newly generated PSD “free edges” represent the synaptic “tags” that initiate LTP ( Frey and Morris, 1997 , 1998a , b ; Martin and Kosik, 2002 ; Redondo and Morris, 2011 ; Shires et al, 2012 ; Evans et al, 2021 ). Although we did not attempt in this study to provide the complete structural evidence for this hypothesis, we predict that it should soon become available from many of the new LM and EM methods that are being developed to “tag” various presynaptic and postsynaptic proteins and protein complexes ( MacGillavry et al, 2013 ; Broadhead et al, 2016 ; Zeng et al, 2016 ; Biederer et al, 2017 ; Chen et al, 2018 , 2020 ; Crosby et al, 2019 ; Trotter et al, 2019 ; Obashi et al, 2021 ; Ramsey et al, 2021 ; Wegner et al, 2022 ). Here, we focused only on providing direct EM images that demonstrated how (and why) enhanced bursts of presynaptic secretory activity apparently create or cause the perforation of otherwise plaque-like postsynaptic densities, in the first place.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…At hippocampal synapses, the postsynaptic densities or PSDs are ordinarily disk-shaped entities that are generally located directly across from presynaptic neurotransmitter release sites ( Gray, 1959 , 1976 ; Blomberg et al, 1977 ; Cohen et al, 1977 ; Cohen and Siekevitz, 1978 ; Carlin et al, 1980 ; Dosemeci et al, 2001 ; Tao-Cheng et al, 2009 ; High et al, 2015 ). They generally appear almost continuous in thickness and density across the breadth of the disk, and even though recent close inspections have begun to suggest that each PSD disk may have a sub-structure, and may be composed of sub-modules or “nanomodules” ( MacGillavry et al, 2013 ; Broadhead et al, 2016 ; Zeng et al, 2016 ; Biederer et al, 2017 ; Chen et al, 2018 , 2020 ; Crosby et al, 2019 ; Trotter et al, 2019 ; Obashi et al, 2021 ; Ramsey et al, 2021 ; Wegner et al, 2022 ), these PSD components pack closely enough together to create the general impression in the EM of a continuous plaque or a disk.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is the integration of learning-related behavioral analysis combined with synapse imaging and ExM. Furthermore, recent in vitro studies revealed the relationship between activity-dependent regulation in synaptic efficacy and dynamic remodeling of synapse nanostructure as a critical component in the regulation of neural circuits (Okabe, 2020a ; Obashi et al, 2021 ). Therefore, identification and nanoscale imaging of synapses involved in learning-related circuit alterations in situ using ExM will benefit the research program of functional neural circuits.…”
Section: Introductionmentioning
confidence: 99%